2017
DOI: 10.1177/1029864917714609
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effect of tempo changes on violinists’ body movements

Abstract: In expressive music performance, tempo is known to be a fundamental parameter. In this article, we explored effects of changes in musical tempo on performers' movement articulations. Eight duos (piano-violin) played two pieces at a predefined tempo, after which this start tempo was gradually increased and decreased. Throughout the different performances, we measured acceleration of the violinists' head and right wrist, together with the downward force applied by their body to the ground surface. We calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…However, for expressive reasons, or for reasons that have to do with musical capabilities, it may happen that a music ensemble's co-regulated timing slightly deviates from the prescribed meter in the score, for example when short notes are performed shorter and long notes are performed longer. Understanding how this timing elasticity relates to musical expressivity is a topic of ongoing research (e.g., Coorevits et al, 2019). Here we see that duet 4 generates an IOI-meter of about {3, 1.5, 1} (in milliseconds ratio) right from the beginning of the performance, while the meter is in fact {3,2,1} (in milliseconds ratio).…”
Section: The Justhockit Datasetmentioning
confidence: 66%
“…However, for expressive reasons, or for reasons that have to do with musical capabilities, it may happen that a music ensemble's co-regulated timing slightly deviates from the prescribed meter in the score, for example when short notes are performed shorter and long notes are performed longer. Understanding how this timing elasticity relates to musical expressivity is a topic of ongoing research (e.g., Coorevits et al, 2019). Here we see that duet 4 generates an IOI-meter of about {3, 1.5, 1} (in milliseconds ratio) right from the beginning of the performance, while the meter is in fact {3,2,1} (in milliseconds ratio).…”
Section: The Justhockit Datasetmentioning
confidence: 66%
“…A similarly synergistic approach has been recently applied to the study of expressive violin-piano duet performance by Coorevits and co-workers (2019) . On the initial premise that tempo is an important variable for a system, they explored the effects of gradual tempo changes on articulatory patterns in the violinists’ body movements (head, right wrist, and body downward force) and showed that continuous changes in performance tempo led to transitions from one order to another characterized by qualitatively distinct bodily articulation patterns.…”
Section: The Dance Of Individuality and Collectivitymentioning
confidence: 99%
“…Interviews (Blum 1987;Boyle 2015;Fink & Merriell 1985;Murnighan & Conlon 1991), ethnographic (Bayley 2011) and practice-based artistic research (Doğantan-Dack 2013; Heyde 2012; Spissky 2017) provide a performer's knowledge of musical interaction, interpretation and intentions behind their gestures. Combining these different approaches of quantitative and qualitative research methods have enhanced the method ological development of artistic research and provided valuable information on musicians' movements and intentions from the first-person perspective (Caruso et al 2016;Coorevits et al 2019;Östersjö 2016).…”
Section: The State Of the Art: The Elements And Ramifications Of Leadingmentioning
confidence: 99%